2014
DOI: 10.1109/tnsre.2013.2260172
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of a Morphing Myoelectric Hand Posture Controller Based on Principal Component Analysis of Human Grasping

Abstract: An ideal myoelectric prosthetic hand should have the ability to continuously morph between any posture like an anatomical hand. This paper describes the design and validation of a morphing myoelectric hand controller based on principal component analysis of human grasping. The controller commands continuously morphing hand postures including functional grasps using between two and four surface electromyography (EMG) electrodes pairs. Four unique maps were developed to transform the EMG control signals in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…Previously, we found that a specific mapping of the EMG signals in the PC domain augmented the ability of subjects to drive a VH into functional postures when using the principal components derived by Santello et al [31]. This work builds upon that finding by developing a novel algorithm for a postural controller that is not dependent on PCA to derive the postural vectors.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previously, we found that a specific mapping of the EMG signals in the PC domain augmented the ability of subjects to drive a VH into functional postures when using the principal components derived by Santello et al [31]. This work builds upon that finding by developing a novel algorithm for a postural controller that is not dependent on PCA to derive the postural vectors.…”
Section: Introductionmentioning
confidence: 65%
“…The postural controller presented here integrates several novel aspects with respect to previous work [24][25][26]31]. Here, the postural map is fully customizable due to the novel derivation of the JAT.…”
Section: Novel Aspectsmentioning
confidence: 99%
“…Controller 3 (C3) was a postural controller based on previous work by the authors (Figure 3) [14]. * The architecture used EMG signals like a joystick to morph the hand posture.…”
Section: Controller 3: Postural Controllermentioning
confidence: 99%
“…For example, an intuitive interface would measure the contraction from the flexor or extensor digitorum muscles in order to close or open the digits of a prosthetic hand [6]. MECs for multigrasp prostheses implement different control architectures such as pattern recognition [7][8][9], finite state machines [10][11][12], and postural control (PC) schemes [13][14][15] that transform user intent in the form of EMG signals to motor commands sent to a prosthesis. Pattern recognition systems exploit artificial intelligence algorithms (such as artificial neural networks, fuzzy logic algorithms, support vector machines, etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation